ÙÙØØ© Ø¹Ù ØªØ·ÙØ± Ø§ÙØµØØ§ÙØ© Ø§ÙØ¹Ø±Ø¨ÙØ© - mulyawan, sopwan (EL-IBTIKAR, 2014)
Arabic journalism or press is still rare on discussion and writing in Indonesia, but anyway, it is seemingly similar toÂ  the other parts of world about the beginning of journalism or press, chiefly in development countries. It could be obviously seen in the fact of journalism track ortimelineof each country. In general that the press system in different countries or nations primary inÂ  thedevelopment countries started from authoritarian system, and eventually they came to a press democratic system. But even now on theÂ  authoritarian system still exist in monarchy state, such as Saudi Arabia.Study of Jounalism, especially Arabic journalism has become highlightÂ  of Arab countries, since Egypt was the pioneer of study, as the result of France colony penetration onÂ  it. Teaching journalism was main focus for several new independent countries or developed countries, even though, early it seemed difficult for major Arab countries to determine curriculum content and study program or faculty as a part of educational planning of the country.Â Ø§ÙÙÙÙØ§Øª Ø§ÙØ£Ø³Ø§Ø³ÙØ©: Ø§ÙØµØØ§ÙØ© - Ø¹ÙÙÙØ© Ø§ÙØ¯Ø±Ø§Ø³Ø§Øª Ø§ÙØµØÙÙØ© - Ø¹ÙÙ Ø§ÙØ¯ÙØ§ÙØ©- Ø§ÙÙØÙØ± Ø§ÙÙØ¸ÙÙ - Ø§ÙÙØÙØ± Ø§ÙØ§Ø³ØªØ¨Ø¯Ø§ÙÙ â Ø§ÙØ¨ÙÙÙÙØ© â Ø§ÙØªØÙÙÙ Ø§ÙØ¯ÙØ§ÙÙ -Â  Ø§ÙØªØÙÙÙ Ø§ÙØ£Ø³ÙÙØ¨Ù - Ø§ÙÙØ¸Ø§Ù Ø§ÙØµØÙÙ Ø§ÙØ³ÙØ·ÙÙ - Ø§ÙÙØ¸Ø§Ù Ø§ÙØµØÙÙ Ø§ÙÙÙØ¨Ø±Ø§ÙÙ - Ø§ÙÙØ¸Ø§Ù Ø§ÙØµØÙÙ Ø§ÙØ§Ø´ØªØ±Ø§ÙÙ Ø§ÙØµÙÙÙÙØªÙ - Ø§ÙÙØ¸Ø§Ù Ø§ÙØµØÙÙ Ø§ÙÙØ³Ø¦ÙÙÙ Ø§ÙØ§Ø´ØªØ±Ø§ÙÙ - Ø§ÙÙØ¸Ø§Ù Ø§ÙØµØÙÙ Ø§ÙØªÙÙÙÙ - Ø§ÙÙØ¸Ø§Ù Ø§ÙØµØÙÙ Ø§ÙØ¯ÙÙÙÙØ±Ø·Ù Ø§ÙÙØ´ØªØ±Ù